Design Of a System Feeding, Vitamin, Drinking and Cage Cleaning for Chicken Coops Based on Android Applications - Maharani, Zahra habibah; Mustafa, Lis Diana; Junus, Mochammad (Politeknik Negeri Malang, 2023)
The food filling system in raising chickens is still relying on human power. Breeders must regularly check on everything in the cage. In addition, if the farmer forgets to check it will be fatal and will affect chicken production. The research method will be carried out by monitoring feeding, drinking, vitamins and cleaning cages when ammonia gas is detected which increases above 50. Where in previous studies it was still done manually. Automatic control will be carried out using a microcontroller as the command brain and processing sensor data on the system. Where the trigger for cleaning is based on the ammonia level, while for feed it is based on the volume of the place to feed and drink. The weight sensor has an accuracy rate of 99.9% while the range is 99.13%. For the measurement of chicken manure ammonia gas can be done with a reading accuracy level of 99.69%. After using this system, the value of weight and gas content of Ammonia decreases from the first day to the third day. From the 3-day test, the highest value of ammonia gas content was obtained at a value of 197.56 ppm with a weight of 9.8 grams. The lowest was obtained on the third day with ammonia gas content of 18.37 ppm with a weight of 2.1 grams. For network quality, the system has an average delay of 0.07580 seconds and the packet loss obtained when testing is 6.11% (Very Good).